PROFESSOR Ó.ÁLEWOV ILIMIY-PEDAGOGIKALÍQ MEKTEBINIŃ PEDAGOGIKA ILIMINDEGI ORNÍ - Utebaev, T.T. (ILIM hám JÁMIYET, 2025)
The article deals with Honored Science Worker, Ph.D, professor Oserbay Aleuov`s life and pedagogical experience and importance of his educational views.